Hip Abductor and Adductor Rate of Torque Development and Muscle Activation, but Not Muscle Size, Are Associated With Functional Performance - Lanza, Marcel Bahia; Rock, Kelly; Marchese, Victoria; Addison, Odessa; Gray, Vicki L. (Frontiers in Physiology, 2021)
Understanding the physiological variables that contribute to a functional task provides important information for trainers and clinicians to improve functional performance. The hip abductors and adductors muscles appear to be important in determining the performance of some functional tasks; however, little is known about the relationship of the hip abductor/adductors muscle strength, activation, and size with functional performance. This study aimed to investigate the relationship of maximum torque, rate of torque development (RTD), rate of activation (RoA), and muscle thickness of the hip abductors [tensor fascia latae (TFL) and gluteus medius (GM)] and adductor magnus muscle with the Four Square Step Test (FSST) and the two-leg hop test in healthy young adults. Twenty participants (five males) attended one testing session that involved ultrasound image acquisition, maximal isometric voluntary contractions (hip abduction and hip adduction) while surface electromyography (EMG) was recorded, and two functional tests (FSST and two-leg side hop test). Bivariate correlations were performed between maximum voluntary torque (MVT), RTD at 50, 100, 200, and 300ms, RoA at 0–50, 0–100, 0–200, and 0–300, and muscle thickness with the dynamic stability tests. For the hip abduction, MVT (r=−0.455, p=0.044) and RTD300 (r=−0.494, p=0.027) was correlated with the FSST. GM RoA50 (r=−0.481, p=0.032) and RoA100 (r=−0.459, p=0.042) were significantly correlated with the two-leg side hop test. For the hip adduction, there was a significant correlation between the FSST and RTD300 (r=−0.500, p=0.025), while the two-leg side hop test was correlated with RTD200 (r=0.446, p=0.049) and RTD300 (r=0.594, p=0.006). Overall, the ability of the hip abductor and adductor muscles to produce torque quickly, GM rapid activation, and hip abductor MVT is important for better performance on the FSST and two-leg hop tests. However, muscle size appears not to influence the same tests.